1993
DOI: 10.1128/aem.59.9.2801-2806.1993
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a recombinant wine yeast strain expressing beta-(1,4)-endoglucanase and its use in microvinification processes

Abstract: A genetic transformation system for an industrial wine yeast strain is presented here. The system is based on the acquisition of cycloheximide resistance and is a direct adaptation of a previously published procedure for brewing yeasts (L. Del Pozo, D. Abarca, M. G. Claros, and A. Jimenez, Curr. Genet. 19:353-358, 1991). Transformants arose at an optimal frequency of 0.5 transformant per ,ug of DNA, are stable in the absence of selective pressure, and produce wine in the same way as the untransformed industria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(33 citation statements)
references
References 26 publications
3
29
0
1
Order By: Relevance
“…So, enzymatic degradation of the cell wall by carbohydrolases (pectinase, cellulase, xylanase and glucanase) contributes to the release of those precursors from the berries to the must. It has been proposed that the cell wall degradation of the grapes allows many aromatic or potential aromatic compounds to form part of the must, resulting in a better aromatic profile (Pérez-González et al 1993). Our results showed that the only non-Saccharomyces species where the four carbohydrolases activities were present was L. thermotolerans, and this species was the only one showing xylanase activity.…”
Section: Enzymes Related With Aromamentioning
confidence: 51%
“…So, enzymatic degradation of the cell wall by carbohydrolases (pectinase, cellulase, xylanase and glucanase) contributes to the release of those precursors from the berries to the must. It has been proposed that the cell wall degradation of the grapes allows many aromatic or potential aromatic compounds to form part of the must, resulting in a better aromatic profile (Pérez-González et al 1993). Our results showed that the only non-Saccharomyces species where the four carbohydrolases activities were present was L. thermotolerans, and this species was the only one showing xylanase activity.…”
Section: Enzymes Related With Aromamentioning
confidence: 51%
“…Likewise, glucanolytic wine yeasts have been developed by expressing glucanase genes in S. cerevisiae. These are Butyrivibrio fibrisolvens endo-β-1,4glucanase gene (END1), the Bacillus subtilis endo-β-1,3-1,4-glucanase gene (BEG1), the Ruminococcus flavefaciens cellodextrinase gene (CEL1), the Phanerochaeta chrysosporium cellobiohydrolase gene (CBH1) and the Saccharomycopsis fibuligera cellobiase gene (BGL1) (Pérez-González et al 1993, Van Rensburg et al 1994, 1996, Petersen et al 1998, Van Rensburg et al 1998, 2005. Xylanolytic yeasts were developed by expressing the following gene cassettes in S. cerevisiae: the endo-β-xylanase genes from Aspergillus kawachii (XYN1) (Crous et al 1995); Aspergillus nidulans (xlnA and xlnB) (Pérez-González et al 1996); Aspergillus niger (XYN4 and XYN5) (Luttig et al 1997) and Trichoderma reesei (XYN2) (La Grange et al 1996Grange et al , 2001; the xylosidase genes from A. niger (xlnB) and Bacillus pumilus xylosidase (XLO1) (La Grange et al 1997); and the A. niger α-L-arabinofuranosidase gene (ABF2) (Crous et al 1996).…”
Section: Improving Wine Processingmentioning
confidence: 99%
“…The initial yeast inoculum was of 2.5 × 10 5 cells/mL from YPD overnight cultures. Bottles were incubated at 22°C with gentle orbital agitation (125 rpm) without aeration (Pérez-González et al, 1993). Where specified, microvinification was carried out at 30°C with orbital agitation at 175 rpm.…”
Section: Yeast Strains Media and Growth Conditionsmentioning
confidence: 99%
“…To analyze fermentative ability microvinifications were carried out (Pérez-González et al, 1993) using natural must (Moscatel, Requena, Spain, 1997) at 22°C. Under these conditions the strains LYCC 047, LYCC 082, and T 73 were able to ferment all the glucose present within 6 days (data not shown).…”
Section: Analysis Of the Fermentation Process Carried Out By The Winementioning
confidence: 99%